PENGEMBANGAN PERMAINAN TRADISIONAL MPA’A LAPE UNTUK MENINGKATKAN KREATIVITAS MAHASISWA PADA MATA KULIAH T & P BULU TANGKIS - Hidayat, Taufiq; Pratama, Sandi Achmad; Susila, Linda; Daracau, Alfin (LPPM Institut Pendidikan Nusantara Global, 2023)
Badminton course is one of the compulsory subjects taught in the STKIP Yapis Dompu Physical Health and Recreation Education study program ideally, in the learning process students will not only learn material related to badminton techniques, but also with traditional games that heve regional culture in Bima-Dompu. There are several factors that cause students to find in difficult to undersand material related to badminton courses, namely empahasizing mastery of the material and methods taught using lecture, discusssion, power point and LCD methods taught so far. Less effective for practical courses, due to limited facilities owned by students, used is mpa’a lape The purpose of this research is to produce the traditional game to increase student creativity in the T & P Badminton course using the Borg and Gall model, media validity was obtained from the results of expert validation consisting of two material experts with the stage I validation questionnaire on experts material I 95% and material experts II. 91.66% and the validation is done by media experts. Media experts II 95%. Phase II validation questionnaire material expert I 96% and material expert II 96%. Questionnaire calculationon student responses are given. Media experts I. 95% and media experts II 95% with the criteria “ Veri suitable for use “ the practicality of the media was obtained throught a questionnaire responding to class A students of the Physical Education Health and Recreation Study Program for the 2023-2024 academic year of 2023-2024 by 95 % with the criteria “ Very suitable for use” The conclusion that Mpa’a Lape Traditional games to increase student crativity in T &P Badminton courses is valid and practically used in badminton courses.